Characteristics of Brain Imaging in Intracranial Tumor Patients at Neurology Ward Dr. Hasan Sadikin General Hospital Bandung 2017–2019 - Putri Nur Amalia Dewi; Asep Nugraha Hermawan; Cep Juli; Paulus Anam Ong; Sofiati Dian (Althea Medical Journal, 2021)
Background: Brain imaging is the main modality in establishing the diagnosis of intracranial tumors. Therefore, by using appropriate imaging modalities, lesions can be identified and this is useful in determining management and monitoring of the therapeutic process. This study aimed to describe the use of imaging modalities and the characteristics of imaging findings in diagnosing intracranial tumor patients.Methods: This cross-sectional descriptive study obtained data from medical resumes at the Neurology Ward of Dr. Hasan Sadikin General Hospital Bandung, collected by total sampling method. Data on patients with intracranial tumors who underwent imaging examinations in January 2017–December 2019 were taken, including demographical and imaging characteristics data, divided by tumor type.Results: Of 206 data, the imaging modalities used were contrast CT scan (45.6%), non-contrast CT scan (34.5%), multimodality imaging (13.6%), contrast magnetic resonance imaging (MRI) (3.9%), non-contrast MRI (2.4%), and magnetic resonance spectroscopy (MRS) (0.5%). The most common primary tumor was a solitary lesion (89.4%) located in the right hemisphere in 38.1% of subjects. Metastatic tumors were found mostly as multiple lesions (63.4%) located in both supratentorial and infratentorial in 25.8% of the subjects. Perifocal edema was found in 75% of patients in both tumor types.Conclusions: Contrast CT scan is the most frequently used imaging modality. The most common radiological finding is perifocal edema. Primary tumors are commonly found in solitary numbers, and are located in supratentorial on the right hemisphere. Metastatic tumors are commonly found in multiple numbers and are located both in supratentorial and infratentorial.